Various complexes of the oral microbial flora in periodontal disease - Sukhvinder Singh Oberoi; Shabina Sachdeva; Shibani Grover (Journal of Dental Problems and Solutions - Peertechz Publications, 2021)
Periodontal diseases, is the infection of the periodontal tissues which eventually can lead to loss of teeth, is a form of aberrant inflammation resulting from a complex biofilm of friendly commensal and periodontopathic bacteria and their products, triggering the human inflammatory response. The cluster analysis has shown that 6 closely associated bacterial complexes are associated with it which are designated with different color codes. The early colonizers are "Blue complex" consisting of Actinomyces species, "Yellow complex" comprising of various Streptococci, "Green complex" comprising Eiknella corrodens and Capnocytophaga species, and "Purple complex" comprising Veillonella parvula and Actinomyces odontolyticus. The late colonizers are "Orange complex" comprising Prevotella, Fusobacterium, Campylobacter and other bacteria and the "Red complex" chiefly consisting of Porphyromonas gingivalis, Tannerella forsythia, and Treponema Denticola.